Impact of first medical contact to revascularisation time on long-term clinical outcomes in ST-segment elevation myocardial infarction patients (Swiss Medical Weekly, 2020)
INTRODUCTION We sought to identify predictors for a prolonged delay from first medical contact to revascularisation (FMC-R) in ST-segment elevation myocardial infarction (STEMI) patients at our institution and to assess the impact of a prolonged treatment delay on 3-year clinical outcome. MTHODS EVALFAST is a prospective and retrospective registry enrolling all patients admitted directly from pre-hospital care to the catheterisation laboratory at Fribourg Hospital for suspected STEMI, starting in June 2008. Relevant patient and procedural data were collected retrospectively and prospectively. Clinical follow-up was performed by phone or clinic visit. Patients were divided into two groups: FMC-R interval